ANALISIS PENGARUH WEB QUALITY, FULFILLMENT, TERHADAP KEPUASAN DAN DAMPAKNYA PADA MINAT BELI ULANG (Studi Kasus Pada Pelanggan Tokopedia di Kota Pontianak) - Ute, Damianus Ute B1021161068 (Jurnal Manajemen Update, 2020)
ABSTRACTThe purpose of This study is to discuss and analyze the influence of Web Quality, Fulfillment, and Satisfaction and Its Impact on Repurchase Intention of Tokopedia Customers in Pontianak City. This type of research uses quantitative methods, the population in this study are all Tokopedia consumers in Pontianak City . The sample in this study used 100 respondents using purposive sampling technique and the data analysis carried out with Path Analysis. T test results of the first substructure Fulfillment, Web Quality variable, significantly influence Satisfaction. The second substructure of the Fulfillment variable, does not significantly influence the Repurchase Intention while the Web Quality and Satisfaction variables significantly influence the Repurchase Intention.Keywords: Web Quality, Fulfillment, Satisfaction, and Repurchase IntentionDaftar PustakaBarnes, S.J., & Vidgen, R.T. (2002). Assessing e-commerce quality with WebQual: An evaluation of the usability, informaton quality, and interaction quality on Internet bookstores. Journal of Electronic Cormerce Research, 3, 114-127Blut, et al. (2016). E-Service Quality: A Meta-Analitic Review. Journal of Retailing, 91 (4).Ferdinand, A. (2002). Pengembangan Minat Beli Merek Ekstensi. Semarang: Badan Penerbit Universitas Diponegoro.Ghozali, I. (2011). Aplikasi Analisis Multivariate Dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Huyen Pham & Thu Nguyen (2019). The Effect Of Website Quality On Repurchase Intention With The Mediation Of Perceived Value: The Case Study Of Online Travel Agencies In Vietnam. Journal Of Global Business Insights. 4 (1).Jain, K.N., et al. (2017). E-fulfillment dimensions and its influence on customers in e-tailing: a critical review. Asia Pacific Journal of Marketing and Logistic, 29 (2).Jauhari, M. T., Kusumawati, A., & Nuralam, I. P. (2019). The Impact of Website Quality on Consumer Satisfaction and Purchase Intention (Study Case of E-Commerce Lazada Indonesia in Malang City). Jurnal Administrasi Bisnis, 67 (1).Koufteros, et al. (2014), Encounter satisfaction in e?tailing: are the relationships of order fulfillment service quality with its antecedents and consequences moderated by historical satisfaction. Decision Sciences, 45, (1). 5-48Kurniawati, Kusyanti & Murssityo (2018). Analsis Pengaruh Kualitas Website Terhadap Kepuasan Pelanggan Mister Aladin Dengan Menggunakan Webqual 4.0. Jurnal Pengembangan Tekonologi Informasi Dan Ilmu Computer, 2 (3). 1151-1160Lathiras, et al. (2011). Assessing The Impact Of Website Quality On User Satisfaction: A Study Of Webqual And Net Promoter Score In Hotels. 4th Annual EuroMed Conference Of The EuroMed Academy Of Business, pp. 1058-1073 Lovelock, C., & Wirtz, J. (2011). Perspektif Pemasaran Jasa edisi 7. Jakarta: Erlangga SaputriMuhsin, A., & Zuliestiana, D. A., (2017). Analisis Pengaruh Kualitas Website (WebQual) 4.0 Terhadap Kepuasan Pengguna Bukalapak di Kota Bandung. e-Proceeding of Management, 8 (3). Parasuraman, A., Zeithaml, V.A., & Malhotra, A. (2005). E-S-QUAL: A Multiple-item Scale for Assessing Electronic Service Quality. Journal of Service Research, 7 (3).Ranjbarian, Bahram, et al. (2012). An Analysis Of Brand Image, Perceived Quality, Customer Satisfaction and Re-Purchase Intention in Iranian Department Stores. Journal of Business and Management. 7 (6).Rinaldi, A. & Santoso, S.B. (2108). Analisis Pengaruh Kualitas Informasi, Kualitas Sistem Dan Kualitas Pelayanan Terhadap Minat Beli Ulang Dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Pelanggan Traveloka di Kota Semarang). Diponegoro Journal of Management,7 (2)Rohwiyati & Praptiestrini (2019). The Effect Of Shopee E-Service Quality And Price Perception On Repurchase Intention: Customer Satisfaction As Mediation Variable. Indonesian Journal Of Contemporary Management Research, 1 (1).Saputri, D.M., & Astuti, R.T. (2016). Analisis Faktor-Faktor Yang Mempengaruhi Minat Beli Ulang Produk Customcase Handphone dengan Kepuasan Pelanggan Sebagai Variabel Intervening. Diponegoro Journal of Management, 5 (3)Schiffman, L.G., & Kanuk, L.L. (2010). Consumer Behaviour (10th ed). New Jersey: Pearson Prentice Hall.Supriyantini, Suyadi, I., & Riyadi. (2014). Pengaruh Efficiency, Fulfillment, System Availability, dan Privacy terhadap satisfaction. Jurnal Administrasi Bisnis (JAB), 5 (2).Sugiyono. (2017). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: CV. Alfabeta.Tjiptono, F. (2014). Pemasaran Jasa, Prinsip, Penerapan, dan Penelitian. Yogyakarta: Andi Offset.Wahidin, A. (2013). Analisis Kepuasan Mahasiswa Terhadap Website Universitas Negeri Yogyakarta (UNY). Skripsi Jurusan Pendidikan Teknik Mesin Fakultas Teknik Universitas Negeri Yogyakarta.